O documentário poético performático e a voz do corpo dançante como inter(trans)texto de si mesma: Pas de Deux Wenders-Bausch - Wosniak, Cristiane do Rocio (2015)
In this thesis, which is titled as O documentário poético performático e a voz do corpo dançante como inter(trans)texto de si mesma: pas de deux Wenders-Bausch [The poetic and performative documentary and the voice of the dancing body as an inter(trans)text of itself: pas de deux Wenders-Bausch], I discuss an overlap between dance and cinema through use of a semiotic process of film analysis. The main goal of this paper is to ponder upon the question that generated this research: how and by use of which elements the kinetic iconic voices of the dancing body presented in the documentary ‘Pina’ directed by Wim Wenders in 2011 (which in itself is a poetic and performative tribute to the choreographer Pina Bausch) are inter(trans)texts of themselves and are opened to polysemic meanings? Using the examples drawn from hypotexts presented or indicated in the hypertext ‘Pina’ as a gathering of voices that act as an inter(trans)text in/by the process of saying/performing dance, I apply the Gérard Gennette’s theory of transtextuality and the explicitness of ways and means by which they appear in the corpus chosen for this study, intending to present - through use of decoupage of excerpts of the nonverbal text – the nature of the multiple voices presented in the empirical object in analysis. This thesis follows the idea that in the transposition of a text or of hypotextuals (pre-existing) voices into another text (hypertextualised) there is an exchange, the unceasing semiosic movement of the transit from one signifying system to another, and, in this dynamic process of analysis is based the argument sustained in this study that happen different inter(trans)textuals interfaces, which embodied/dancing voices comprise a net or mosaic in the definition of the hypertext taken in consideration. This study was developed based on the theories of Charles Sanders Peirce (mainly in his Speculative Grammar), Gilles Deleuze and Gérard Gennette. Also, to clarify the concept of the iconic voice presented by/in the body it was used the theoretical discussions of Bill Nichols and Fernão Pessoa Ramos. In Chapter 1 the poetic and performative documentary is presented as a text and the theories of Gennette based the understanding of transtextuality that are applied to the corpus of this investigation. In Chapter 2 is established the concept of voice and clarified the poetic and performative modal types assigned to the documentary. In the final chapter dance and cinema are compared and overlap the Deleuze’s ontology of time-image for proposing pure conditions of vision and sound (opsigns and sonsigns) and for comprehending cinema as an idea as well as a result of the difference.